Family Functioning and Risk Factors in the Development of Behavioral Disorders in Adolescents - Ecuador, Español; Español, Español (Revista Universidad de Guayaquil, 2025)
The general objective of this research was to identify the relationship between family functioning and risk factors in the development of behavioral disorders in adolescents. The methodology used was quantitative, descriptive correlational, cross-sectional and non-experimental design. The following instruments were used: cohesion and flexibility scale (FACES III) and questionnaire for the detection of behavioral disorders in children and adolescents (ESPERI). 109 adolescents of both sexes between 14 and 16 years of age participated in the study. The most significant findings were the following: 80,07% of the adolescents had dysfunctional family functioning, while 41,3% presented a mild level of risk factors in the development of behavioral disorders. Therefore, the most relevant conclusion is that there is no relationship between family functioning and risk factors in the development of behavioral disorders, this was due to the influence of protective factors, such as, the presence of positive role models, the support of teachers or mentors and peer support networks that counteracted the negative effects of poor family functioning.
Keywords: Family functioning; Behavioral disorders; Adolescence; Risk Factors